Isolation And Identification of Ligninolytic Fungi from South Gujarat Region - Vashi, Riddhi S.; Dholaria, Mayuri (International Journal of Applied Sciences and Biotechnology, 2025)
Adequate amount of lignocellulosic biomass on earth features convincing feedstock material for various sustainable products such as bioplastics, biofuels and biomedical applications. However, delignification is necessary for converting complex material into valuable products. Among various pretreatment methods, biological delignification is particularly attractive due to its environmental friendliness. Ligninolytic fungi from Ascomycota and Basidiomycota are the primary target due to their secretion of oxidative enzymes like Laccase, LiP, and MnP, which initiate the degradation of its stable structure. Isolation, screening, and identification of potential ligninolytic fungi is an aim of this investigation. A total of 18 various fungal strains were isolated by using potato dextrose agar medium from 15 different collected environmental samples. Through quantitative and qualitative screening, three potential fungi labelled as F5, F8, and F9, were selected and identified as Fusarium chlamydosporum (PX482664), Polyporus benetostus (PQ348730), and Trichoderma erinaceum (PQ349085) using the ITS region-based molecular method. The Laccase activity of F-5, F-8, and F-9 were found to be 261.32 U/g, 434.29 U/g, and 207.67 U/g, respectively, while their LiP activity was determined to be 503.1 U/g, 430.5 U/g, and 330.6 U/g, respectively. However, no MnP activity was observed in all three fungal cultures.Int. J. Appl. Sci. Biotechnol. Vol 13(4): 162-170.